Optimized nano-transfersomal films for enhanced sildenafil citrate transdermal delivery: ex vivo and in vivo evaluation - Badr-Eldin SM; Ahmed OAA (Dove Medical Press, 2016)
Shaimaa M Badr-Eldin,1,2 Osamaa AA Ahmed1,3 1Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, King Abdulaziz University, Jeddah, Kingdom of Saudi Arabia; 2Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Cairo University, Cairo, Egypt; 3Department of Pharmaceutics and Industrial Pharmacy, Faculty of Pharmacy, Minia University, Minia, Egypt Abstract: Sildenafil citrate (SLD) is a selective cyclic guanosine monophosphate-specific phosphodiesterase type 5 inhibitor used for the oral treatment of erectile dysfunction and, more recently, for other indications, including pulmonary hypertension. The challenges facing the oral administration of the drug include poor bioavailability and short duration of action that requires frequent administration. Thus, the objective of this work is to formulate optimized SLD nano-transfersomal transdermal films with enhanced and controlled permeation aiming at surmounting the previously mentioned challenges and hence improving the drug bioavailability. SLD nano-transfersomes were prepared using modified lipid hydration technique. Central composite design was applied for the optimization of SLD nano-transfersomes with minimized vesicular size. The independent variables studied were drug-to-phospholipid molar ratio, surfactant hydrophilic lipophilic balance, and hydration medium pH. The optimized SLD nano-transfersomes were developed and evaluated for vesicular size and morphology and then incorporated into hydroxypropyl methyl cellulose transdermal films. The optimized transfersomes were unilamellar and spherical in shape with vesicular size of 130 nm. The optimized SLD nano-transfersomal films exhibited enhanced ex vivo permeation parameters with controlled profile compared to SLD control films. Furthermore, enhanced bioavailability and extended absorption were demonstrated by SLD nano-transfersomal films as reflected by their significantly higher maximum plasma concentration (Cmax) and area under the curve and longer time to maximum plasma concentration (Tmax) compared to control films. These results highlighted the potentiality of optimized SLD nano-transfersomal films to enhance the transdermal permeation and the bioavailability of the drug with the possible consequence of reducing the dose and administration frequency. Keywords: sildenafil citrate, central composite design, transfersomes, edge activator, permeation, transdermal, pharmacokinetics